Correlação entre saúde periodontal e idade gestacional - Mascarenhas, Vinícius Ibiapina [UNESP]; Vilarinho, Laís Aires Lima; Moura, Lúcia De Fátima Almeida De Deus; Moura, Marcoeli Silva De; Ferro, Leonardo Borges (Universidade Estadual Paulista Júlio de Mesquita Filho, 2012)
INTRODUCTION: The birth of newborn (NB) underweight is considered a public health problem and is often associated with prematurity. The etiology of preterm birth is complex and often is related to several factors. Several theories have correlated the periodontal health of pregnant women with preterm birth (gestational age) and / or with low birth weight. OBJECTIVE: The objective of this study is to evaluate the possible correlation between periodontal health with gestacional time and/or with low birth weight. MATERIAL AND METHOD: A Prospective longitudinal observational study with pregnant women that were attending a extension project of UFPI - Preventive Program for Pregnant Women and Babies - PPPWB. Data collection was structured in two moments: 1st fill sheet containing questions related to health of the pregnant woman, complete clinical and periodontal examination of the oral cavity and 2nd data collection on the type of delivery, gestation length, baby's weight and health condition. RESULT: A total of 62 pregnant women were attended and only 43 patients participated in the second moment of the study. There was a predominance of women aged between 25 to 35 years (55.81%). The bleeding index ranged from 1.19% to 92.50%. The average weight of infants was 3365.33 g and gestational time was 39.33 weeks. CONCLUSION: The results of this study did not support the hypothesis that periodontal disease is associated with gestacional time and/or low birth weight.

INTRODUÇÃO: O baixo peso de recém-nascidos (RN) é considerado um problema de saúde pública e, geralmente, é associado à prematuridade. A etiologia do parto prematuro é bastante complexa e, frequentemente, está relacionada a vários fatores. Diversas teorias têm correlacionado a saúde periodontal de gestantes com o nascimento de bebês prematuros (idade gestacional) e/ou com baixo peso ao nascer. OBJETIVO: O objetivo do presente estudo foi avaliar a possível correlação de saúde periodontal com idade gestacional e/ou com nascimento de bebês com baixo peso. MATERIAL E MÉTODO: Estudo observacional longitudinal prospectivo com gestantes que foram atendidas em um projeto de extensão da Universidade Federal do Piauí - Programa Preventivo para Gestantes e Bebês - PPGB. A coleta dos dados foi estruturada em dois momentos: 1º- Preenchimento de ficha contendo dados relativos à saúde geral e exame periodontal completo, e 2º- Coleta de dados referentes a tipo de parto, duração da gestação, peso e condição de saúde do bebê. RESULTADO: De 62 gestantes atendidas, 43 participaram do segundo momento do estudo. Ocorreu uma predominância de gestantes com idade entre 25 e 35 anos (55,81%). O índice de sangramento gengival variou de 1,19% a 92,50%. A média do peso dos bebês foi 3.365,33 g e do tempo gestacional foi 39,33 semanas. CONCLUSÃO: Os resultados deste estudo não deram suporte à hipótese de que a doença periodontal está associada à idade gestacional.
Correlation between periodontal health and gestacional age
Keywords: Periodontics; premature; low birth weight; Periodontia; prematuros; baixo peso ao nascer